2019
DOI: 10.2215/cjn.13221118
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing of a Sick-Day Protocol in CKD

Abstract: Assessing the performance at self-management of patients with CKD is essential for effective strategies to safeguard care. We evaluated the use of a sick-day protocol with structured usability testing by patients with CKD. The Sick-Day Protocol is a selfmanagement protocol developed by National Health Service Highland in Scotland to prevent AKI, and it is made available through the Scottish Patient Safety Program on a "Medicine Sick Day Rules" card (1). The Sick-Day Protocol card describes a gastrointestinal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 2 publications
1
18
1
Order By: Relevance
“…Not all signalled they would do this after 24 h; some preferred contacting a health professional immediately or within the first 24 h of acute illness. A study by Doerfler et al [ 18 ] showed participants accurately identified the scenario that qualified for Sick‐Day Protocol implementation, but most (95%) made a medicine selection error, compared with 10% in our study. Inappropriate timing of restarting medicines or permanent discontinuation is also potential risks.…”
Section: Discussioncontrasting
confidence: 80%
“…Not all signalled they would do this after 24 h; some preferred contacting a health professional immediately or within the first 24 h of acute illness. A study by Doerfler et al [ 18 ] showed participants accurately identified the scenario that qualified for Sick‐Day Protocol implementation, but most (95%) made a medicine selection error, compared with 10% in our study. Inappropriate timing of restarting medicines or permanent discontinuation is also potential risks.…”
Section: Discussioncontrasting
confidence: 80%
“…In preparation for this trial, we conducted usability testing of the sick-day protocol card as designed by the Scottish Patient Safety Programme and reported a range of failures in understanding and errors with its simulated use. 22 We made modifications to the sick-day protocol and associated card and distributed it for use in conjunction with an IVRS platform for reminders of protocol engagement among sick-day protocol participants. The discrepancy between participant enthusiasm to use the sick-day protocol, evidenced by high rates of IVRS interaction, and the ability to successfully identify sick days and implement sick-day protocol instructions illustrates the challenges common with patient education materials.…”
Section: Discussionmentioning
confidence: 99%
“…In preparation for this trial, we conducted usability testing of the sick-day protocol card as designed by the Scottish Patient Safety Programme and reported a range of failures in understanding and errors with its simulated use 22 . We made modifications to the sick-day protocol and associated card and distributed it for use in conjunction with an interactive voice response system platform for reminders of protocol engagement among sick-day protocol participants.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…At this stage usability testing is also carried out on the developed system. Usability testing itself is carried out to find out how easy it is for users to use the developed system so that system developers know the end users' difficulties in using the system and find out the shortcomings of the developed system [27]. To determine user satisfaction with the developed system, the measurement uses the following equation: In addition to end-user satisfaction, the level of effectiveness and efficiency of the developed system also needs to be measured to determine the success rate of the system using the user's success rate, which is the percentage of tasks completed correctly by the end-user [28].…”
Section: Methodsmentioning
confidence: 99%
“…For the measurement of self-satisfaction using equation ( 1) [34]. While the measurement of the level of effectiveness and efficiency of the system uses equation ( 2) [27]. Previously, the questionnaires distributed to 27 respondents were analyzed, as shown in the following table: The results of measuring the level of satisfaction, the level of effectiveness and efficiency of the plastic waste management website at PT.…”
Section: IIImentioning
confidence: 99%